PENGARUH KESELAMATAN KESEHATAN KERJA (K3) DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Arwin Saputra; Indra Kusdarianto; Samsinar - (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to determine the success of a company is largely determined by the good and bad performance of employees. This could have happened because of the influence of Occupational Health Safety (K3) and the Work Environment, this study employed a quantitative methodology. A survey will be the methodology used in this study. A questionnaire was employed as the data collecting tool for this study to gather data on indicators linked to the research variables and the sample population under examination. Amount of samples used in this study 77 respondents. The data analysis technique used in this study was the IBM Statistics SPSS 20 For Windows program. The research data were analyzed descriptively. The results of the research conducted show that the Occupational Health Safety (K3) and Work Environment variables have a positive and significant effect on employee performance. This can be seen from the value of Adjusted R Square = 0.253 or 25.3%.